Impact of frequency of feedline soaking combined with evaporative air cooling in a humid environment - John F. Smith; D.V. Armstrong; M. J. VanBaale; D.R. Bray (Kansas Agricultural Experiment Station Research Reports, 2005)
Heat stress in hot and humid environments reduces milk production, decreases reproduction, and increases health-related problems. The summertime environment in north-central Florida is especially difficult because the combination of high relative humidity and high temperature results in a temperaturehumidity index (THI) above the critical value of 72 for significant portions of the day. Previous work at Kansas State University had shown that the combination of soaking and evaporative air cooling could effectively cool heat-stressed cattle. Effectiveness of this feedline soaking, either in the afternoon and at night, or only at night, in combination with evaporative cooling was evaluated on a commercial dairy located in north-central Florida. A high-pressure fogging system and feedline soakers were installed in a typical 4-row freestall barn equipped with tunnel ventilation creating a north to south airflow of 6 to 8 mph at the cow level. Eight lactating Holstein cows in each of two, 292-stall pens were selected and fitted with vaginal temperature probes. Data on vaginal temperature and respiration rate were used to evaluate two cooling treatments. Barn temperature averaged 74.8 ± 5.4ºF, relative humidity was 84.6 ± 15.4 %, and THI was 74.7 ± 5.3 during the study. The evaporative cooling system reduced average barn temperature by 0.9ºF and reduced afternoon temperatures by a maximum of 9.2ºF. Average respiration rates were less (58.5 vs. 66.9 breaths/min) in the afternoon and night soaking treatment, compared with the respiration rate of cattle in the night soaking treatment. Differences were greatest at the 10:00 p.m. observation (55.0 vs. 73.3 breaths/min). Average vaginal temperature was also less (102.0 vs. 102.6°F) in the afternoon and night soaking treatment. Our results indicate that the combination of cooling the air via a highpressure fogging system and feedline soaking reduced heat stress experienced by dairy cattle. Using feedline soaking during the afternoon and night was more effective than soaking only at night.; Dairy Day, 2005, Kansas State University, Manhattan, KS, 2005; Dairy Research, 2005 is known as Dairy Day, 2005
Keywords: Dairy Day; 2005; Kansas Agricultural Experiment Station contribution; no. 06-46-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 963; Dairy; Cow comfort; Cow cooling; Heat abatement